Demystifying the NIOSH equation for multi-tasks: a practical roadmap application - Moura, Henrique Martim de (2022)
The NIOSH equation is disseminated and used in Brazil by professionals and academics. However, one of the main problems is applying the NIOSH Equation for simple task contexts characterized as multi-tasks. Nevertheless, there is an important gap in these works in demonstrating the most didactic use of them. Thus, the present work is described as a case study. The NIOSH equation was applied following five methodological steps in a multi-task common in the context of macro markets and supermarkets. We conclude that using NIOSH Equation for multi-tasks provided that it is done sparingly and using the correct values of frequencies during the calculation procedures. Can bring a more accurate assessment of the risks related to the maintenance of loads in complex activities, avoiding misperceptions of work situations and, consequently, damage to workers' health.